INTERVENSI DINI BERBASIS SEKOLAH BAGI ANAK ADHD - Puja Dwi Sonia (Universitas Karimun Prodi S1 Pendidikan Luar Biasa, 2023)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurobiological disorder or behavior disorder that is most often found in children. The main symptoms of ADHD consist of inattention (concentration disorders. Most (80%) children with ADHD will continue these symptoms into their teens, even into adulthood. Children with ADHD are at risk of becoming adults with antisocial and criminal disorders, substance abuse (alcohol and drugs), emotional problems, social maladaptation, educational and work failures, interpersonal disorders and personality disorders. Children with ADHD also tend to experience rejection and are less accepted in society by their peers, compared to children who do not have ADHD. The number of school children with ADHD today continues to increase.The Diagnosis and Statistics Manual (DSM IV) states that the incidence of ADHD in school-age children ranges from 3 -5%.